Vers un modèle multiscalaire des territoires frontaliers intérieurs à l’Union européenne - Grégory Hamez (Belgeo, 2013)
The paper proposes a theoretical multiscalar model of border territories in the European Union, based on a definition of territory encompassing the three dimensions of the spatial practices, representations and governance, through the lens of three spatial scales to interpret the cross border functioning (local, national, European). The model opens up research perspectives to grasp the complexity of border processes in terms of disjunction between the spatial scales of phenomena occurrences, as well as between the territorial action levels.